Maternal Systemic Interleukin-6 During Pregnancy is Associated with Newborn Amygdala Phenotypes and Subsequent Behavior at 2-years-of-age - Graham, Alice M. (Biol Psychiatry, 2017)
BACKGROUND: Maternal inflammation during pregnancy increases risk for offspring psychiatric disorders and other adverse long-term health outcomes. The influence of inflammation on the developing fetal brain is hypothesized as one potential mechanism, but has not been examined in humans. METHODS: Participants were N=86 adult women recruited in early pregnancy, and their infants born after 34-weeks gestation. A biological indicator of maternal inflammation (interleukin-6 [IL-6]), which has been shown to influence fetal brain development in animal models, was quantified serially in early, mid and late pregnancy. Structural and functional brain MRI was acquired in neonates shortly after birth. Infants’ amygdalae were individually segmented for measures of volume and as seeds for resting state functional connectivity. At 24-months-of-age, children completed a snack delay task to assess impulse control. RESULTS: Higher average maternal IL-6 concentration during pregnancy was prospectively associated with larger right amygdala volume and stronger bilateral amygdala connectivity to brain regions involved in sensory processing and integration (fusiform, somatosensory cortex, thalamus), salience detection (anterior insula), and learning and memory (caudate and parahippocampal gyrus). Larger newborn right amygdala volume and stronger left amygdala connectivity were in turn associated with lower impulse control at 24-months-of-age, and mediated the association between higher maternal IL-6 concentrations and lower impulse control. CONCLUSIONS: These findings provide new evidence in humans linking maternal inflammation during pregnancy with newborn brain and emerging behavioral phenotypes relevant for psychiatric disorders. A better understanding of intrauterine conditions that influence offspring disease susceptibility is warranted to inform targeted early intervention and prevention efforts.